2016
DOI: 10.1016/j.cca.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

The majority of lipoprotein lipase in plasma is bound to remnant lipoproteins: A new definition of remnant lipoproteins

Abstract: It is suggested that during lipolysis in vivo, the endothelial bound LPL dimers generates RLP, forming circulating RLP-LPL complexes in an inactive form that subsequently binds and initiates receptor-mediated catabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 52 publications
2
21
1
1
Order By: Relevance
“…Moreover, administration of AG increased plasma low-density lipo- protein 1 (LRP-1), scavenger receptor A1 (SR-A1), and very low-density lipoprotein receptor (VLDLR), to heparin-like substances. 37 In addition, overexpression of macrophage-derived LPL contributes to anchoring some atherogenic lipoproteins, such as LDL and oxLDL, thereby promoting cellular lipid uptake and accumulation. In the present study, HDAC9 was identified as a direct target of miR-182, which is consistent with a recent report.…”
Section: Effects Of Mir-182 On Proinflammatory Cytokines and Lipids Imentioning
confidence: 99%
“…Moreover, administration of AG increased plasma low-density lipo- protein 1 (LRP-1), scavenger receptor A1 (SR-A1), and very low-density lipoprotein receptor (VLDLR), to heparin-like substances. 37 In addition, overexpression of macrophage-derived LPL contributes to anchoring some atherogenic lipoproteins, such as LDL and oxLDL, thereby promoting cellular lipid uptake and accumulation. In the present study, HDAC9 was identified as a direct target of miR-182, which is consistent with a recent report.…”
Section: Effects Of Mir-182 On Proinflammatory Cytokines and Lipids Imentioning
confidence: 99%
“…We previously reported that the particle size of remnant lipoproteins were inversely correlated with LPL activity and concentration [36]. Large RLP particles carry a significantly less LPL concentration per particle compared to small RLP particles, as shown by the LPL/RLP-TG ratio [34,35,41]. It is because unchanged concentration of LPL on the endothelium after food intake has to hydrolyze significantly increased CM and VLDL particles.…”
Section: Formation Of Remnant Lipoproteins By Lpl At Endotheliummentioning
confidence: 98%
“…Using the immunoaffinity separation method of remnant lipoproteins, we found that the majority of LPL in plasma presented in RLP fraction which we isolated as remnant lipoproteins for many years [35].…”
Section: Discovery Of Rlp-lpl Complex In Plasmamentioning
confidence: 99%
See 2 more Smart Citations